High resolution photovoltaic power generation potential assessments of rooftop in China. (November 2022) - Wang, Lichao; Xu, Shengzhi; Gong, Youkang; Ning, Jing; Zhang, Xiaodan; Zhao, Ying
Abstract: Rooftop photovoltaic system plays an important role in solar energy power generation especially in urban. In this paper, we present an assessment method for the PV power generation potential of rooftop in China. Using machine learning model processes the big data that consists of the gross domestic product, building footprint, road length and population, at a high geographic resolution of 10 km by 10 km. The result shows that the rooftop generation potential in China is 3.27×10 9 MWh annually, which is close to half of the total electricity generation of China mainland in 2020, and will contribute to 2.41×10 9 tons of CO2 emission reduction per year. The regional results are counted by provinces and cities, showing Shandong province is the one with highest potential of 0.275×10 9 MWh. On the whole, the western region covers a large area with sufficient solar radiation, while the eastern region has greater photovoltaic power generation potential because of its available roof resources. The development potential of first tier, new first tier and second tier cities is generally greater than that of third and fourth tier cities. Highlights: A high-resolution solar photovoltaic potential map of China utilizes the open dataset and one novel neural network model. The data are stated by provinces and cities showing the regional differences. The rooftop photovoltaic generation will be closed to half of the electricity generation of China mainland in 2020. The eastern region has great accumulated photovoltaic electricity potential, which is 3.21 times that of the western region.